Willingness to pay a price premium for energy-saving appliances: Role of perceived value and energy efficiency labeling. (1st January 2020) - Zhang, Yixiang; Xiao, Congcong; Zhou, Guanghui
Abstract: Energy consumption has caused major crises and severe global challenges, such as environmental problems and climate change. Household appliances are highly utilized products that consume considerable electricity. The wide adoption of energy-saving appliances saves power resources and promotes the development of low-carbon economy. However, energy-saving appliances are usually more expensive than ordinary household appliances, thereby hindering their widespread adoption. Therefore, the factors influencing consumers' willingness to pay a price premium for energy-saving appliances should be explored. A comprehensive model was constructed based on the theory of planned behavior and consumer perceived value literature. The influencing factors were identified in terms of product, consumer, and regulation and publicity. Data were collected through questionnaire survey method, as it is suitable for collecting data on human beliefs and perceptions. 327 valid responses were obtained from the survey, and the data were analyzed using partial least squares. Results show that consumers' attitude toward purchasing energy-saving appliances positively impacts willingness to pay a price premium. Consumer perceived quality, price, emotional, and environmental values significantly and positively impact consumers' purchasing attitude. Furthermore, the perceived effectiveness of energy efficiency labeling institutional mechanism and personal norm significantly and positively influences consumers' purchasing attitude. Nevertheless, social value, environmental awareness, and media publicity do not significantly affect consumers' purchasing attitude. Finally, suggestions on how to promote energy-saving appliances were proposed. Highlights: Determinates of willingness to pay a price premium for energy-saving appliances are identified. The concept of perceived effectiveness of energy label institutional mechanism is proposed. Dimensions of perceived value of energy-saving appliances are identified.